2014
DOI: 10.1021/jo500577c
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the β-Thiolactones: Substituent and Solvent Effects on Thermal Decomposition and Comparison with the β-Lactones.

Abstract: The synthesis of a series of di-, tri-, and tetraalkyl β-thiolactones and β-lactones is described as well as their thermal decomposition with extrusion of carbon oxysulfide and carbon dioxide in two solvents of opposite polarities. The β-thiolactones are considerably more thermally stable than the β-lactones and require higher temperatures for efficient decomposition in both solvents, whatever the degree of substitution. The results are interpreted in terms of a zwitterionic mechanism for fragmentation with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 85 publications
2
10
0
Order By: Relevance
“…Several reports have pointed out that the strain energies of cyclic molecules are influenced by heteroatom substitution or functionalization. 32 35 Thus, our results are comparable to these reports. The influence of substitution with the halogen atoms is quite minimal when compared to the heteroatom effect on the CHP ring.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Several reports have pointed out that the strain energies of cyclic molecules are influenced by heteroatom substitution or functionalization. 32 35 Thus, our results are comparable to these reports. The influence of substitution with the halogen atoms is quite minimal when compared to the heteroatom effect on the CHP ring.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Further control experiments demonstrated that thiolactone 49 can be converted into alkene 50 by prolonged heating under reflux in ethanol although this thermal reaction did not proceed as cleanly as the photochemical olefination process. Interest in the thermal decomposition process has gained further interest in recent years [34] . A similar result was obtained for the reaction of N ‐methyldithiophthalimide 51 with the ketene (using equal equivalents of each reagent), although more dethiocarboylation product was obtained.…”
Section: Intramolecular Radical Routes For Thiolactone Synthesissupporting
confidence: 54%
“…Encouraged by this, thioester 2a was hydrolyzed to deprotect the thiol and carboxylic acid moiety, furnishing 5-mercaptopentanoic acid. The free thiol was then immediately subjected to Steglich cyclization conditions, modified slightly from conditions previously reported for the synthesis of β-thiolactones . To the thiol in anhydrous CH 2 Cl 2 under dilute conditions were added 2 equiv of the carbodiimide coupling reagent EDC·HCl and 1.2 equiv of the nucleophilic catalyst 4-(dimethylamino)­pyridine (DMAP).…”
mentioning
confidence: 89%
“…Thiolactones represent an underexploited class of sulfur-containing heterocyclic compounds with potential application in numerous fields, although of late they have garnered increased interest. β-thiolactones, although somewhat unstable, have drawn considerable attention for their ability to mediate the coupling of sterically demanding peptides by native chemical ligation . γ-Thiolactones have proven useful in chemical biology, , medicinal chemistry, drug discovery, and materials science, , with the γ-thiolactones derivatives of homocysteine thiolactone (Hcy-thiolactone), the product of homocysteine metabolism, of particular interest (Figure ).…”
mentioning
confidence: 99%